Weighing patient attributes in antibiotic prescribing for upper respiratory tract infections: A discrete choice experiment on primary care physicians in Hubei Province, China - Xue, Tianqin; Liu, Chaojie; Li, Zhuoxian; Liu, Junjie; Tang, Yuqing (Frontiers in Public Health, 2022)
Objectives: This study aimed to determine how primary care physicians weigh intervenable patient attributes in their decisions of antibiotic prescribing for upper respiratory tract infections (URTIs). Methods: A discrete choice experiment (DCE) was conducted on 386 primary care physicians selected through a stratified cluster sampling strategy in Hubei province, China. The patient attributes tested in the DCE were identified through semi-structured interviews with 13 primary care physicians, while the choice scenarios were determined by a D-efficient design with a zero prior parameter value. Conditional logit models (CL) and mixed logit models (MXL) were established to determine the preference of the study participants in antibiotic prescribing for URTI patients with various attributes. Relative importance (RI) was calculated to reflect the influence of each attribute. Results: In addition to age and duration of symptoms, the interventionable patient attributes were also considered by the primary care physicians in their antibiotic prescribing decisions. They preferred to prescribe antibiotics for URTI patients with difficulties to schedule a follow-up appointment (p<0.001) and for those without a clear indication of refusal to antibiotics (p<0.001). Patient request for antibiotics had an RI ranging from 15.2% to 16.3%, compared with 5.1% to 5.4% for easiness of follow-up appointment. The influence of these two interventionable patient attributes was most profound in the antibiotic prescribing decisions for patients aged between 60 and 75 years as indicated by their interaction effects with age (β=0.69 for request for antibiotics, p<0.01; β=-1.2 for easiness of follow-up, p<0.001). Conclusion: Reducing patient pressure and improving accessibility and continuity of care may help primary care physicians make rational antibiotic prescribing decisions for URTIs.